Serum antibody responses in human periodontitis to cellular components of Capnocytophaga - Dyer, J K; Reinhardt, R A; Petro, T M; Strom, E A (Archives of oral biology, 1992)
Serum levels of IgM, IgG and IgG-antibody subclasses directed against cell envelopes, lipopolysaccharides and cytoplasmic fractions from Capnocytophaga sputigena, C. gingivalis and C. ochracea were examined in age-, race- and sex-matched periodontally healthy (n = 25) subjects and subjects with adult periodontitis (n = 25). The envelopes and cytoplasmic fractions were obtained by ballistic disintegration of the cells and ultracentrifugation. Cell envelopes were treated with DNase, RNase and lysozyme. Lipopolysaccharides were obtained by hot phenol-water extraction and treated with DNase and RNase. The relative levels of the antibodies in response to the cell fractions were measured by the streptavidinbiotin micro enzyme-linked immunosorbent assay. Both groups showed IgM and IgG antibodies to each fraction of the three Capnocytophaga species, but the frequency of positive IgG subclass responses varied. The IgG4 responses were lower than the other subclasses. There were no significant differences between the IgM antibody levels of the two groups. However, the adult periodontitis group had significantly lower IgG antibody titres to the cell envelopes and cytoplasmic fractions of C. gingivalis and C. ochracea, and lipopolysaccharide of C. gingivalis. These results were reflected in the depressed levels of IgG1 and/or IgG2 to these cellular fractions from the same bacterial species. The adult periodontitis group also showed a lower level of IgG1 to the cytoplasmic fractions of C. sputigena without any depression in the total IgG antibody level. There were no significant differences between the groups in IgG3 and IgG4 antibody levels to any of the cellular fractions.